Utilization of Admixtures in Self-Compacting High Performance Concrete (International Journal of Innovative Research in Computer Science & Technology, 2020)
Flowable concrete or self-consolidating or  self-compacting concrete (SCC) is a particularly flowable,  non-segregating concrete which flows, plugs formwork,  and captures the utmost congested rebars with none use of  mechanical vibration. When used with admixtures to  enhance the performance of concrete, it is called as  self-compacting high performance concrete. An extant  literature survey was taken up to understand the utilization  of waste polyethene, fly ash and micro-silica in SCC to  make it a SCHPC. It has been seen that very less amount of  research work is available on use of waste polythene in  conventional concrete as well as SCC. A few studies have  reported positive results towards the mechanical properties  i.e. compressive strength and flexural strength of concrete  while no literature is available taking into account its initial  cost and the durability aspects of such concrete.
Keywords: SCC; concrete; high performance; flowable; construction